Pemanfaatan Internet pada Matakuliah Ilmu Pendidikan di Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palangka Raya - Jasiah Jasiah (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
The aims this study is the utilization of Internet media by students on science subjects in Faculty of Teacher Training and Science Teaching State Islamic Institute Palangka Raya. The method used in this research is the Mixed Method, which is a merger between quantitative and qualitative methods in a single study. Data collection techniques are observation , interviews and questionnaires. The data analysis technique that is editing, tabulating, analyzing and concluding. The results of this study are based on the results of questionnaires known that 36 students obtained information about the level of utilization of the Internet as a source of learning in the subjects of science education as follows: 8 students (22.22%) criteria very well, 18 students (50.00%) criteria, 10 students (27.78%) criteria good enough, 0 students (0.00%) said that the use of the internet as a learning resource study science subjects in the criteria is not good and is not very good. Students use the Internet as a source of learning ,. because with the Internet can assist students in finding information and tasks subjects Education Sciences. If there is no task that many in the college access is facebook, google, yahoo, twitter and youtube.. Factors supporting the use of the Internet as a source of student learning, among others, the demands of the lecturers to fulfill the tasks subjects Education, learning resources available on the internet is more complete, helps the reviewer got the course, making it easier to perform tasks, the existing information more clearly and valid, faster in search of information, resources realy more complete knowledge, the existence of hotspots on campus, which is up to date news / new, lower-cost, easily accessible, curiosity and needs.